The first Dugesia species (Platyhelminthes, Tricladida, Dugesiidae) documented for Saudi Arabia: an integrative description - Harrath, Abdel Halim; Mansour, Lamjed; Sluys, Ronald; Aldahmich, Waleed; Riutort, Marta; Alwasel, Saleh (Zootaxa, 2025)
Exploration of various freshwater bodies in the Kingdom of Saudi Arabia led to the discovery of a new species of Dugesia, thus representing the first documented record of freshwater planarians in this country and the second fully documented record of a naturally sexual population of a Dugesia species in the Arabian Peninsula. Based on morphological, karyological, anatomical, and molecular data, this Dugesia population from Saudi Arabia is here identified as representing a distinct, new species, Dugesia bursagrossa Harrath & Sluys, sp. nov. The species is characterized by the following anatomical features: dorsal testes; highly glandular, barrel-shaped penis papilla; vasa deferentia opening separately into the antero-dorsal portion of a small intrabulbar seminal vesicle; ejaculatory duct opening subterminally through the ventral side of the penis papilla; muscular penis bulb composed of intermingled longitudinal and circular muscles; two ovaries positioned ventrally at approximately one-third of the distance between the brain and the root of the pharynx; oviducts opening separately and at different levels into the vaginal portion of the bursal canal; very large copulatory bursa, occupying almost the entire ample space between the posterior wall of the pharyngeal pocket and the penis bulb; bursal canal lined with a nucleated epithelium and covered by subepithelial layers of longitudinal muscles, followed by layers of circular muscles. The karyotype of the new species exhibits mixoploidy, with diploid complements of 2n = 18 and triploid complements of 3n = 27 + 1B chromosomes, with all chromosomes being metacentric. Phylogenetic analysis based on the COI sequence indicates that D. bursagrossa is distinct from closely related species within the same clade, with strong support from the anatomical and karyological data.